PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH ( PBM ) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 18 BABUSSALAM KECAMATAN MANDAU - Helma '; Hendri Marhadi; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the lack of student learning outcomes IPS, it can be seen from the results of social research Elementary School fourth grade students Babussalam 18, with the average value of the class 63.60. Therefore, the researchers provide an alternative learning for the implementation of the model Problem Based Learning (PBM) in the fourth grade SDN 18 Babussalam. This study aims to improve learning outcomes IPS fourth grade students of SD Negeri 18 Babussalam Implementation of Problem Based Learning Model (PBM). Design research is action research (PTK) with two cycles. Based on the analysis of research data after applying the model of Problem Based Learning (PBM), the average percentage of activity the teachers in the first cycle of 82.5% increased to 92.5% in the second cycle. The average percentage of student activity also increased, namely 77.5% in the first cycle increased to 87.5% in the second cycle. learning outcomes in basic score with the average value of 63.60 and the first cycle of students increased by an average value of 72.66 with an increasing percentage of classroom learning achievement of 12.46% and the percentage of students who completed 76.66%, and the second cycle increased again to an average of 77.33 with the percentage improvement class learning outcomes 13.73% and the percentage of students who completed 83.33%. These results suggest that application of the model of Problem Based Learning (PBM) can improve learning outcomes IPS fourth grade students of SD Negeri 18 Babussalam Key Words: Problem Based Learning, learning outcomes IPS